A new double-antigen sandwich test based on the light-initiated chemiluminescent assay for detecting anti-hepatitis C virus antibodies with high sensitivity and specificity - Li, Haicong; Yang, Shuo; Cao, Dan; Wang, Qianying; Zhang, Siyu; Zhou, Yi; Liu, Di; Yang, Ruifeng; Cui, Liyan; Zhu, Zhaoqin (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives: To evaluate the performance of a new double-antigen sandwich test that is based on the light-initiated chemiluminescent assay (LiCA ® ) for detecting anti-hepatitis C virus antibodies (anti-HCV) in comparison of Architect ® .Methods: Analytical characteristics and diagnostic performance were tested using seroconversion panels and large pools of clinical samples. Positive results were validated by the strip immunoblot assay (RIBA) and HCV RNA.Results: Repeatability and within-lab imprecision of LiCA ® anti-HCV were 1.31 3.27%. The C5 C95 interval was -5.44% 5.03% away from C50. LiCA ® detected seroconversion in an average of 28.9 days and showed mean 3.7 (P=0.0056) days earlier than Architect ® . In a pool of 239 samples with known HCV genotypes 1 to 6, both assays correctly detected all subjects. In 16,305 clinical patient sera, LiCA ® detected 4 false-negative (0.25‰) and 14 false-positive (0.86‰) anti-HCV cases, while Architect ® recorded 6 false-negative (0.37‰) and 138 false-positive (8.46‰) subjects, respectively. Compared to Architect ® , LiCA ® presented a significantly better performance in specificity (99.91% vs. 99.14%, n=16,018, P<0.0001), positive predictive value (95.29% vs. 67.06%, n=419, P<0.0001) and overall accuracy (99.89% vs. 99.12%, n=16,305, P<0.0001), while no significant difference in sensitivity (98.61% vs. 97.91%, n=287, P=0.5217) and negative predictive value (99.98% vs. 99.96%, n=15,886, P=0.3021). A S/Co value of 3.28 was predicted to be the threshold with a positivity ≥95% for the LiCA ® anti-HCV assay.Conclusions: LiCA ® anti-HCV is a precise and fully automatic chemiluminescent assay with superior sensitivity and specificity. The assay can be used as a valuable tool to supplement the diagnosis of HCV infection.